Depresión en Mujeres como Consecuencia del Impacto del Embarazo Post Parto, en una IPS de Maicao- La Guajira
The objective of this research is to analyze Postpartum Depression in Wayuu Women in a Health Service Provider Institution. The methodology is based on a mixed approach, with a sequential explanatory design and a descriptive type, a sample of 48 women was collected (48 for a survey and 8 for a semi-structured interview), the questionnaire and interview technique was used as data collection. and also, the descriptive statistics technique for quantitative analyzes in conjunction with content analysis in semantic matrix as qualitative analysis, the instruments were the Edinburgh Test and semi-structured interview. As a result, it was found that 58% of the participating women are at risk of suffering from postpartum depression, reporting symptoms of sadness, anxiety, guilt, irritability, sleep problems and thoughts of self-harm. Regarding the interviews, at a qualitative level it was found that women can suffering from risk factors such as lack of emotional and socioeconomic support, family conflicts. It is concluded that it is necessary to improve the living conditions of women to mitigate the effects or prevent the development of postpartum depression.